Pengaruh gaya kepemimpinan dan motivasi terhadap semangat kerja di PT. Kalbe Nutritionals Medan Amplas - Khamo Waruwu; Uswatun Hasanah; Elyani Elyani; Mastini Lase (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study was to determine the significant influence of leadership style and motivation on morale at PT Kalbe Nutritinals and to find out which factors were more dominant which became the morale of work. This research is located at PT Kalbe Nutritonals which is located at Enseval Building, Gg. Madirsan KM 9.5, Weigh Deli, Medan Amplas, Medan City. This study uses multiple regression analysis technique with a sample size of 40 people. From the results of the partial test (t test) leadership style and motivation affect work morale at PT Kalbe Nutritionals because it has a tcount > ttable and a significant value less than a probability value of 0.05, From the results of the simultaneous test (Test F) together leadership style and Motivation affect work morale at PT Kalbe Nutritionals seen from the significance level of 0.000 < 0.05, the determination value (R2) of 65.1% indicates between each the independent variable with the dependent has a close relationship, while the remaining 34.9% are influenced by other variables.